REFORMULASI PENATAAN OVERCROWDING LEMBAGA PEMASYARAKATAN DI INDONESIA MELALUI PENYELESAIAN PERKARA PIDANA BERBASIS KEADILAN RESTORATIF - Shafa Azzahra Rizal (2023)
Data from the Ministry of Law and Human Rights as of 12 September 2021 shows that the total number of inmates in prisons throughout Indonesia has reached 271,007 people. In fact, the capacity of prisons in 33 Regional Offices are only for 134,835 people. That means, there is excess capacity or overcrowding of prison inmates as many as 136,173 people, which is twice the total, 101% to be precise. Imprisonment is still the most commonly used form of punishment for perpetrators in Indonesia. Gradually it was proven that punishment with the aim of retaliation could in fact not have a deterrent effect on the perpetrators. So that currently the paradigm of punishment is starting to change from being retributive to being restorative. In this study the authors also look at the implementation of out-of-court settlements that have been implemented in other countries as a reference and comparison. The research method used in this paper is a normative juridical method, with statutory, conceptual and comparative approaches. Meanwhile, based on the results of the research, it is known that the implementation of the settlement of criminal cases outside the court based on restorative justice in various countries has succeeded in becoming an alternative settlement of cases. In Indonesia, restorative-based justice is also implemented, as well as being the government' effort to reduce the number of prison inmates. Especially now that there have been several new arrangements contained in the Criminal Code and the laws that support its implementation. Keywords: Restorative Justice, Prison Overcrowding, Non-Custodial Settlement.